Розширення горизонтів: вивільнення сили уяви та творчого мислення. Рецензія на: Kind, A. (2022). Imagination and Creative Thinking. Cambridge Elements: Philosophy of Mind. Edited by Keith Frankish. Cambridge: Cambridge University Press. 64 pp. - Ярощук, Катерина; Yaroshchuk, Kateryna (Видавництво Львівської політехніки, 2024)
Новаторська праця Емі Кайнд «Уява та креативне мислення», опублікована Кембриджським університетом, досліджує складний зв’язок між уявою та процесами творчого мислення. Це дослідження забезпечує комплексне та ґрунтовне дослідження фундаментального впливу уяви на людське пізнання. Заглиблюючись у складність цієї фундаментальної когнітивної здатності, авторка пропонує розглянути цінне джерело творчості.

Amy Kind’s groundbreaking work, «Imagination and Creative Thinking» published by Cambridge University, explores the intricate relationship between imagination and the processes of creative thinking. This research provides a comprehensive and insightful exploration of the profound impact imagination has on human cognition and innovation. By delving into the complexities of this fundamental cognitive ability, Kind’s work proposes to consider a valuable wellspring of creativity.
Expanding Horizons: Unleashing the Power of Imagination and Creative Thinking. Review of: Kind, A. (2022). Imagination and Creative Thinking. Cambridge Elements: Philosophy of Mind. Edited by Keith Frankish. Cambridge: Cambridge University Press. 64 pp.
Keywords: уява; мислення; творчість; нововведення; відкриття; креативний штучний інтелект; imagination; creativity; thinking; innivation; discovery; creative artifitial intelligence